From Stigma to Stardom: The Rise of Women in Commercial Performing Arts During the Colonial Period in the Dutch East Indies - Fitriyani Fitriyani (Indonesian Historical Studies, 2025)
This study departs from the strong social stigma attached to women involved in the performing arts during the colonial period in the Dutch East Indies. Within patriarchal and colonial moral constructions, female performers were often associated with deviance, sensuality, and transgressions of domestic norms. Although a number of studies have examined the careers of female artists or representations of women in colonial performing arts, systematic analyses tracing the historical transformation from stigma to professional legitimacy within the context of modern commercial theater remain limited. Employing the historical method, this study demonstrates how women negotiated their positions from marginalized and denigrated figures to central actors on the theatrical stage. The findings show that the modernization of commercial theater (through managerial, aesthetic, and production innovations) introduced by groups such as Miss Riboet’s Orion and Dardanella fostered the emergence of a more professional and competitive performance arena. Business competition and agendas of artistic renewal strengthened women’s positions as leading figures in theatrical productions. As modern theater developed, women who had previously been regarded as low-status entertainment workers gained public recognition as stage stars and symbols of prestige. Women’s images thus shifted from objects of stigma to respected professional subjects within the colonial performing arts industry.Keywords: women, commercial theater, stigma, primadonna, Dutch East Indies, performing entertainment, toneel.